Tác động của việc Trung Quốc gia nhập WTO đối với xuất khẩu hàng hoá của Việt Nam - Đỗ, Kim Chi (2011)
Tác giả: Đỗ Kim Chi, ThS; Hoàng Thị Vân Anh, ThS; Nguyễn Việt Hưng, ThS; Phạm Hồng Lam, CN -- Từ khóa: Trung Quốc; WTO